2022
DOI: 10.1155/2022/7146947
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Evaluation of the Biomechanical Accommodations to Bolus Volume during Human Swallowing

Abstract: Bolus volume is very important in the biomechanics of swallowing. By noninvasively characterizing swallow responses to volume challenges, we can gain more knowledge on swallowing and evaluate swallowing behavior easily. This study aimed to evaluate the impact of bolus volume on the biomechanical characteristics of oropharyngeal swallowing events with a noninvasive sensing system. Fifteen healthy male subjects were recruited and instructed to swallow 5, 10, and 15 ml of water. The sensing system consisted of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Considering the swallowing motion trajectory and its anatomic location variations, some studies have acquired swallowing signals at the suprasternal notch 24,25 . However, the majority of signal acquisitions utilized sensors positioned around the cricoid cartilage of the neck [26][27][28][29][30][31][32][33][34][35][36] . Takahashi et al 37 conducted the first comprehensive study of collection sites and found that the optimal detection site (site 1) was located at the lower edge of the cricoid cartilage, bilaterally in the trachea.…”
Section: Collection Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Considering the swallowing motion trajectory and its anatomic location variations, some studies have acquired swallowing signals at the suprasternal notch 24,25 . However, the majority of signal acquisitions utilized sensors positioned around the cricoid cartilage of the neck [26][27][28][29][30][31][32][33][34][35][36] . Takahashi et al 37 conducted the first comprehensive study of collection sites and found that the optimal detection site (site 1) was located at the lower edge of the cricoid cartilage, bilaterally in the trachea.…”
Section: Collection Sitementioning
confidence: 99%
“…Beyond individual differences, several studies have examined the effect of swallowing tasks on swallowing sounds. Li et al 33 compared acoustic differences in swallowing sounds across different volumes of bolus. Youmans and Steirwalt 36 reported on the characteristics of duration, intensity, and frequency associated with swallowing sounds at different concentrations of nudges.…”
Section: Characteristics Of Swallowing Soundsmentioning
confidence: 99%